Network governance in addressing climate change: a case study of the Asian Cities Climate Change Resilience Network (ACCCRN) in Indonesia. Issue 1 (April 2021) - Kristanti, D; Yudiatmaja, W E; Rezeki, S R I; Yudithia; Samnuzulsari, T; Suyito; Safitri, D P; Akbar, D
Abstract: The Asian Cities Climate Change Resilience Network (ACCCRN) is an international institution assisting the Indonesian government to address climate change by incorporating many institutions. Nevertheless, we still lack an understanding of how the network is established in the process of handling climate change between ACCCRN and related agencies in Indonesia. This paper examines network governance during the involvement of ACCCRN in Indonesia. The purpose of the paper is to explore the network established by the ACCCRN in helping the Indonesian government to reduce the impact of climate change. We used a desk study by employing secondary sources to identify the actors, the relationship among the actors, and the outcome of the networks. We suggest that ACCCRN has played a crucial role in reducing the impact of climate change by cooperating with various organisations in Indonesia. In doing so, there are a number of public and non-profit agencies encompassed in the process of collaboration. This study recommends the government to maintain and increase numerous partnerships between international and local institutions in arranging climate change.